The struggle of the Lithuanian Communist Party for the working people’s children in bourgeois Lithuania - Savickytė , V. (Psichologija, 1969)
The Lithuanian Communist Party was the only party to take care of the working people’s children. With the help of the Comsomol the Party fought for the improvement of the conditions of life, work and education of the working people’s children, took care of their political-ideological education. The Party paid much attention to the activity of the Young Pioneer Organization - the Communist organization of the working people’s children.